Analysis of Sexual Health of Adolescents Living in Residential Centers Based on Experts' Opinions - Jazini, Shadi; Namdarpour, Fahimeh; Amanelahi, Abbas (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of this study was to analyze the sexual health of adolescents living in residential centers based on the opinions of experts in the city of Isfahan.Methods: This qualitative study was conducted using thematic analysis. The participants included sexual health experts from the city of Isfahan, selected through purposive sampling based on inclusion criteria. These individuals were examined using semi-structured interviews, and data saturation was achieved with 10 interviews.Findings: After data analysis and coding, 94 initial codes, 11 axial codes, and 4 core codes were extracted. The core codes included the experience of negative emotions, various sexual disorders, experiences of neglect and rejection in the environment, and incorrect sexual upbringing. The axial codes were classified as feelings of hatred towards one's body due to sexual exploitation and income, belief in one's own badness due to sexual abuse, sexual problems of abused adolescents, inclination towards same-sex attraction, confusion about sexual orientation, sexual abuse of adolescents living in centers, lack of proper sexual education in the adolescents' families, inability to protect oneself due to the absence of support in situations of sexual abuse, compensating for rejection through non-committal sexual-emotional relationships, sexual vulnerability related to insecure attachment, and incorrect sources of sexual information.Conclusion: Based on the findings, it can be concluded that adolescents living in residential centers face sexual health problems. It is recommended that psychologists and supervisors of these centers use the findings of this study to improve the sexual health of adolescents.